2017
DOI: 10.1515/biolog-2017-0134
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of telocytes in the corpus and cervix of human uterus: an immunohistochemical study

Abstract: Over the last few years, researchers have been studying telocytes, recently described interstitial cells, voraciously. This morphological study focused on the immunohistochemical identification of telocytes and the study of their topographical relations in the wall of the human uterine body and cervix. This study attempted to find the most specific and therefore, the most suitable monoclonal antibody for the study of telocytes via the immunohistochemical methods. Tissue specimens from human uteruses were stain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…They express CD 117, CD 34, vimentin [48], ER, and PR [36]. Our own previous experiments also demonstrated that uterine TCs are CD 117 positive in different histological layers of both the uterine body and cervix, with the strongest positivity found in the myometrium [49]. Apart from these typical markers, Hatta et al and Rosenbaum et al demonstrated that uterine TCs are positive for connexin 43 and SK3 channels, respectively [47,50,51].…”
Section: Immunophenotype Of Frs Telocytesmentioning
confidence: 80%
“…They express CD 117, CD 34, vimentin [48], ER, and PR [36]. Our own previous experiments also demonstrated that uterine TCs are CD 117 positive in different histological layers of both the uterine body and cervix, with the strongest positivity found in the myometrium [49]. Apart from these typical markers, Hatta et al and Rosenbaum et al demonstrated that uterine TCs are positive for connexin 43 and SK3 channels, respectively [47,50,51].…”
Section: Immunophenotype Of Frs Telocytesmentioning
confidence: 80%
“…Vimentin is cytoskeletal type III intermediate filament protein found in mesenchymal-derived cells that provides an architectural network for organelles anchoring to cytoplasm [73]. CD117 is a transmembrane receptor tyrosine kinase widely used for TCs identification which is active in proliferation and differentiation [77]. Based on two distinct double-immunostainings for CD34/CD117 and CD34/Vimentin, skeletal muscle TCs were identified in all groups.…”
Section: Discussionmentioning
confidence: 99%
“…The morphological and topographical differences between the majority of these c-kit-positive cells are well known, so the cells should not be mistaken for each other. According to our previous results, immunohistochemical staining for c-kit appears to be the most suitable method for the detection and description of telocytes in the female genital tract (Urban et al 2016;Klein et al 2017).…”
Section: Question 3 Is It Possible To Identify Telocytes Using Monocmentioning
confidence: 96%